The Impact of the Global Financial Crisis on Public Debt in China and Japan - Palczewska , Olga (Studia Oeconomica Posnaniensia, 2014)
This paper examines the impact of the financial crisis on public debt in China and Japan through an analysis of domestic and foreign literature, reports by financial institutions, as well as the World Bank and the International Monetary Fund data. The first part of this paper presents the overall economic situation of the Asia-Pacific region during the financial crisis and its impact on the public finance sector debt of these countries. The debt was found to be lower not only than the average debt of OECD countries, but also lower than world debt. The second part of the article raises the issue of China's public debt. In the years 2008-2010 the amount of local debt in China more than doubled, and the highest increase was in 2009. The next part of the article addresses the issue of Japan's public debt. It has been shown that, as a result of the financial crisis, Japan's national debt increased in 2010 by 8.4% in comparison to 2008, but the impact of the crisis on public debt was smaller than in G7 countries.